EFFECTIVENESS AGAINTS PROMOTION THROUGH INTERNET MEDIA CITRA MCCAFE INDONESIA USING PHP AND MYSQL - Abdul Rahman (Jurnal Sistem Informasi, 2007)
McCafe is a business expansion undertaken by the McDonalds engaged in the fast-food restaurants ( fast food restaurants ), which is currently expand into areas of the coffe shop. One such branch McCafe kemang raya Jakarta which officially opened on June 4, 2007. Author propose to provide alternative media to the promotion of Kemang Raya Jakarta branch McCafe is by making a website contain any information related thereto. This is intended to McCafe improve the image of itself. As for the information provided in this website which only deals with the author to limit information about Kemang Raya Jakarta branch McCafe. First McCafe opened in Espresso Cultural Centre, Melbourne, Australia, In the year 1993. Currently McCafe has been opened in over 18 countries one of which in Indonesia. Many have McCafe established in Indonesia in this case RG ( Regional ), among others, McCafe Sarinah Jakarta branch, branch Basuki Rahmat Surabaya, Bandung and more branches. But for McDonald's International in this case the JV (Join Venture) McCafe kemang Raya Jakarta branch is Indonesia's first   The author proposes a website that provides all the information about McCafe Kemang Raya Jakarta branch. Where the website contains about the products, services and facilities provided to any achieving customer satisfaction (customer satisfaction) and also to improve McCafe image itself. This website also contains a form to submit comments for each visitor to the website, polls and discussion forums.                 In order for the information contained in this website is becoming more widely author expect comments, articles or news from a website visitor who can transmitted directly through this website.